Perancangan Question Answering System E-Marketplace Sigertengah Menggunakan Metode Scrumban (Studi Kasus : Kelompok Pedagang Sigertengah) - Caca Arif Herdian (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Sales activities have been carried out by humans since the beginning of civilization, along with the times, the way they are done is always changing. Form of sales activity is currently developing, namely by using electronic media called E-Commerce and increasingly developing into E-Marketplace. The competition between E-Marketplace is increasingly competitive with various kinds of the best services to satisfy users. The current demand for excellent service to consumers means that Usaha Mikro Kecil dan Menegah (UMKM) must follow developments in information systems and information technology. Sigertengah traders group as an organization in the field of UMKM that sells art objects is certainly required to provide excellent service in managing the buying and selling of art objects. Currently, the information system that has been built based on E-Marketplace is still in the development stage. Information related to art objects offered on the Sigertengah E-Marketplace does not include information about the authenticity or originality of these art objects. This research will discuss about how to design of Question Answering System using Scrumban method and Unified Modeling Language to describe the system design. The result of this research is a model design of Question Answering System E-Marketplace which consists of several aspects including user aspects, software aspects, hardware aspects and internet network scheme aspects of system implementation plans.